POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN KARAKTER ANAK MI DI ERA DIGITAL - Fatimah, Siti; Damaianti, Siska; Eliyati, Eliyati; Ningsih, Lisa Septia; Gusniawati, Selfina (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2023)
This writing is based on the idea of the need for renewal in the learning model of social science as a response to the symptoms of weakening the quality of the process and results of social studies learning in an effort to prepare early students to become good citizens. This writing uses descriptive qualitative research that uses library research methods to obtain data according to the topic of the problem in the study. The data sources taken are journals and relevant references are research quoted from books. The results of the study state that the cooperative learning model can improve the interpersonal intelligence of elementary school students in ips learning. The cooperative learning model can build communication between students by discussing with group friends, students are taught to be able to respect each other, communicate, and students can work together with their groups so that interactions with other students occur.